(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Kartagener syndrome is a rare form of primary ciliary dyskinesia, characterized by a triad of symptoms including situs inversus, chronic respiratory tract infections, and bronchiectasis. Esophageal atresia is a severe congenital anomaly requiring early surgical correction in the neonatal period. The combination of Kartagener syndrome with esophageal atresia is extremely rare and presents significant challenges for early diagnosis and management of newborns. Objective To present and analyze a clinical case of a newborn with a rare combination of Kartagener syndrome and esophageal atresia, paying special attention to the features of diagnosis, surgical treatment, and postoperative management in the context of complex combined congenital pathology. Materials and Methods The article presents a clinical case of a newborn with Kartagener syndrome associated with esophageal atresia. The features of the clinical picture, results of instrumental and laboratory diagnostic methods, as well as the surgical treatment strategy and postoperative management of the patient are described. Special attention is paid to diagnostic difficulties associated with atypical organ arrangement and the high risk of respiratory complications in the early neonatal period. Results In the presented clinical case of a newborn with a rare combination of Kartagener syndrome and esophageal atresia, the following results were obtained: Diagnostic stage: Thanks to a comprehensive preoperative examination (echocardiography, abdominal ultrasound, radiography), situs inversus with a right-sided aortic arch was timely diagnosed, which determined the choice of a left-sided surgical approach. Surgical treatment: Successful correction of esophageal atresia was performed through a leftsided thoracotomy: the tracheoesophageal fistula was closed, and a primary end-to-end esophagoesophagostomy was created. The early postoperative period was uneventful; anastomotic integrity was confirmed by control esophagography on the 9th day. Postoperative complications and their management: On the 20th day, leftsided exudative pleurisy (lymphatic exudate) developed, requiring pleural cavity drainage. Combined therapy was administered: octreotide (10 mcg/ kg for 14 days) and intrapleural administration of the drug “Lymphablock” (for 7 days), which led to adhesion formation and cessation of lymphorrhea. Outcome: Enteral nutrition was restored on the 25th day after surgery. Compensated stenosis of the upper third of the esophagus was diagnosed, not requiring emergency intervention. The child was weaned to spontaneous breathing by the 45th day and discharged home on the 60th day of life in satisfactory condition for outpatient follow-up. Key result: Timely topical diagnosis of organ arrangement anomalies and a multidisciplinary approach allowed for successful surgical correction and management of postoperative complications (chylothorax/lymphatic pleural effusion), despite the high respiratory risk associated with Kartagener syndrome. Conclusion In Kartagener syndrome, thorough echocardiography is necessary to clarify the location of the aortic arch in order to choose the correct surgical strategy (in this case, the side of approach). The clinical case of a newborn with Kartagener syndrome and esophageal atresia demonstrates the diagnostic and therapeutic challenges in the context of complex congenital pathology. Early detection and a multidisciplinary approach can improve the outcomes of surgical treatment and reduce the risks of postoperative complications. Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 1008-1013